La crisis del llamado "Legal Writing" y la renovación de la enseñanza de la escritura en las facultades de derecho argentinas - Legarre, Santiago (2016)
In this article, the authors analyze the current status of legal writing as a university course within the training program for lawyers in Anglo-American schools, with special focus on its crisis. They propose an alternative approach to teaching language to law students through classic literature works and the study of Spanish spelling rules based on the works of the Spanish Royal Academy. Tutorials in small groups to monitor the progress made by students are another important element of the proposal. Mention is also made of the efforts to simplify legal language, especially Plain English, and the incorporation thereof into university courses.\n